Sadiq and the desert star - Nuurali, Siman (Nuurali, Siman. Sadiq., 2020)
Sadiq's father is going on a business trip, but before he goes he tells Sadiq a story of the Desert Star, which fits in perfectly with Sadiq's third grade class field trip to the planetarium, and inspires Sadiq to build a simple telescope to study the stars when his father returns.